Chromosomal alterations in atherosclerotic plaques - Matturri, Luigi (2001)
Alterations of chromosomes 7 and 11 have been involved in the progression of atherosclerosis. Twenty-three carotid endarterectomy specimens were studied for the presence of alterations in chromosomes 7 and 11, and fibroblastic growth factor-3 (FGF-3) gene amplification. Besides classic histological stainings, immunophenotyping of cellular and vascular components and fluorescence in situ hybridization (FISH) were performed. At the caps, unstable plaques (n = 18) showed inflammatory infiltration of macrophages, smooth muscle cells, and T-lymphocytes. Specifically in these regions, the FISH showed varying percentages of trisomy (15/18) and tetrasomy (8/15) of chromosome 7. In four cases polisomy 7 was noted in some nuclei. Monosomy of chromosome 11 and gene amplification of FGF-3 gene was observed. The FISH of the five stable plaques and normal arterial walls showed no chromosome alterations; furthermore, chromosome 3, which is not involved in atherosclerotic progression, presented a normal ploidy of smooth muscle cells in stable and unstable plaques and normal arterial walls. In conclusion, chromosome 7 and 11 alterations and FGF-3 gene amplification are components of unstable plaques, and might contribute to the evolution of stable plaques into complicated plaques.